2008
DOI: 10.1177/0890334408316085
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Composition of Hindmilk Produced by Mothers of Very Low Birth Weight Infants Born at Less Than 28 Weeks' Gestation

Abstract: The objectives of this study were to describe and compare retinol, alpha-tocopherol and gamma-tocopherol, fat, energy, and nitrogen concentrations between the foremilk and hindmilk fractions of 24-hour milk collected by 24 mothers of very preterm (< 28 weeks' gestation) infants and to relate milk vitamins A and E content to maternal vitamin intake. Concentrations of retinol were significantly higher in hindmilk than in foremilk (1.6-fold), as were concentrations of alpha-tocopherol (1.6-fold), gamma-tocopherol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 42 publications
4
35
1
1
Order By: Relevance
“…Instead, lactose is similar to norms (70 g l À1 ), 10,22 and the protein is somewhat lower, (13-18 g l À1 ). 9,10 The investigators performing the analyses of samples in this report followed the same technique used in their previously published reports on milk composition. In addition, they have recently compared the esterified fat analysis with infrared spectophotometric analysis and found good agreement between the two methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, lactose is similar to norms (70 g l À1 ), 10,22 and the protein is somewhat lower, (13-18 g l À1 ). 9,10 The investigators performing the analyses of samples in this report followed the same technique used in their previously published reports on milk composition. In addition, they have recently compared the esterified fat analysis with infrared spectophotometric analysis and found good agreement between the two methods.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] A possible influence of breast massage on milk composition was proposed by Foda et al, 12 who reported total solids, lipids, casein and gross energy increase in milk hand expressed after using a Japanese method of breast massage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For infants feeding at the breast, the first milk extracted from the breast is high in lactose, is sweet to the infant and entices the infant to feed more. The last milk in the breast or expressed near the end of the pumping or feeding session is high in fat and can be over 30 calories per ounce (Bishara et al 2008;Ogechi et al, 2007;Slusher et al, 2003). Feedings of hind milk alone contribute to weight gain in the infant (Ogechi, et al, 2007).…”
Section: Increasing the Caloric Content Of Breastmilkmentioning
confidence: 99%
“…The education of health care professionals who work with mothers and infants regarding the dynamics of breastfeeding is necessary to allow them to effectively assist mothers. The recommendations suggest that every breastfeeding mother should have a health care professional observe at least one feeding while she is in the hospital or birthing center to ensure the proper transfer of milk to the baby and to decrease the risk of premature weaning (Bishara et al, 2008).…”
Section: Cultural and Behavioral Aspects Of Breastfeedingmentioning
confidence: 99%